PROSES PENYUSUNAN RISALAH RAPAT PARIPURNA DEWAN PERWAKILAN RAKYAT KABUPATEN KLATEN - , REVIA AGUSTIN D ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Treatise of a Meeting of the Plenary Session Plenary Session meeting notes should be made as records, documents, and as a reminder of the board members. Treatise Plenary Session can know what decisions are generated to take care of the Local Government Autonomy, and each Meeting Treatise of the Plenary Session to be made. The internship aims to identify and understand the work system at the Office of the Regional Representatives Council Klaten, to find out how the process of making Mechanisms Parliament Plenary Session Meeting Treatise of Klaten. The benefits that can be taken during the internship is a real experience as a candidate for professional workers in terms of both formal and material. Process Plenary Session Treatise of Meeting of Sub-section prepared by the Proceedings and Hearings. Treatise of Meeting Plenary Session contains the entire proceedings until a decision issues discussed in the meeting of the Plenary Session.